ChemInform Abstract: Carbohydrate Nanocarriers in Biomedical Applications: Functionalization and Construction. Issue 51 (December 2015) - Kang, Biao; Opatz, Till; Landfester, Katharina; Wurm, Frederik R.
Abstract: Review: 168 refs.